Global Stability of an epidemic model with vaccine involving stage structure - Al-husseiny , Hassan Fadhil (Iraqi Journal of Science, 2022)
In this paper a mathematical model that analytically as well as numericallythe flow of infection disease in a population is proposed and studied. It isassumed that the disease divided the population into five classes: immaturesusceptible individuals (S1) , mature individuals (S2 ) , infectious individual(I ), removal individuals (R) and vaccine population (V) . The existence,uniqueness and boundedness of the solution of the model are discussed. Thelocal and global stability of the model is studied. Finally the global dynamics ofthe proposed model is studied numerically.